“Rise like two angels in the night:” Sexualized Violence against Queers in American Film - Ralph J. Poole (European Journal of American Studies)
This essay discusses ways both mainstream Hollywood films and independent cinema have addressed sexualized violence against queers. I am looking at a number of significant films that refrain from stereotypically correlating queerness, sexuality, and violence, opting for a critical assessment of this conflation and offering alternative viewpoints, instead. First highlighting the controversies around prominent films such as Cruising and Boys Don’t Cry, I then look at lesser known, but noteworthy examples (e.g. Hedwig and the Angry Inch, The Skinny, Vacationland, and Mysterious Skin), films arising out the independent film movement known as New Queer Cinema. Focusing on the generic conventions, the narrative strategies and aesthetic means of these films, I probe into the ways they aim to affectively engage the audience and discuss their respective cinematic approaches of envisioning justice for people from the LGBTIQ* community who have experienced violence in sexualized contexts.